The Role of Teacher Response and Support in Fostering Smart Risk-Taking Behavior of K-12 Chemistry Students Through Learning Intention - Djoa, Dominikus Djago; Sunyono, Sunyono; Hariri, Hasan; Rahman, Taufik (Jurnal Pendidikan Progresif, 2024)
Abstract: The Role of Teacher Response and Support in Fostering Smart Risk-Taking Behavior of K-12 Chemistry Students Through Learning Intention. Objectives: This study explores how teacher support influences K-12 students' learning intentions and risk-taking in Indonesian chemistry education, aiming to bolster creative and critical thinking. Methods: A quantitative survey aligned with the positivist paradigm examines the dynamics between teacher behaviours, classroom interactions, and students' willingness for intelligent risk-taking. Findings: It reveals the critical role of supportive teaching methods in promoting smart risk-taking, enhancing classroom engagement, and shaping students' educational interests and attitudes. These insights suggest a profound impact on educational practices in chemistry, highlighting the importance of supportive learning environments. Conclusion: The research emphasizes the need for fostering robust teacher-student engagement and creating conducive learning spaces, with broad implications for teacher training, curriculum design, and educational policy. It underscores the value of dynamic, engaging, and effective learning experiences in the chemistry classroom that empower students to take intelligent risks, significantly contributing to their educational development. Keywords: chemistry smart taking behavior; k12 students; learning intention; teacher support and response.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202403